2013
DOI: 10.1159/000356018
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Combined Chemotherapy with 5-Week Cycles of S-1 and CPT-11 plus Bevacizumab in Patients with Metastatic Colon Cancer

Abstract: Objective: Combined chemotherapy with S-1 and irinotecan (IRIS) for metastatic colorectal cancer has been reported to be effective and safe. However, there are only a few studies on the effects of adding bevacizumab to IRIS. We conducted a clinical study to evaluate the efficacy and safety of IRIS plus bevacizumab as first-line therapy for metastatic colorectal cancer. Methods: Forty metastatic colorectal cancer patients were enrolled in this phase II study. All patients received irinotecan (80 mg/m2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In our study, the administered dose of irinotecan was lower. However, recent studies have reported good outcomes with oral S-1 and irinotecan plus bevacizumab, used instead of FOLFIRI plus bevacizumab, in patients with MCRC who had not previously received chemotherapy [30,31,32]. The effectiveness of combination chemotherapy with S-1, irinotecan, and bevacizumab in our study was consistent with the findings of previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, the administered dose of irinotecan was lower. However, recent studies have reported good outcomes with oral S-1 and irinotecan plus bevacizumab, used instead of FOLFIRI plus bevacizumab, in patients with MCRC who had not previously received chemotherapy [30,31,32]. The effectiveness of combination chemotherapy with S-1, irinotecan, and bevacizumab in our study was consistent with the findings of previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, irinotecan was administered in the following doses: 100 mg/m 2 biweekly by Komatsu et al [30], 80 mg/m 2 biweekly by Mizushima et al [32], and 150 mg/m 2 triweekly by Yamada et al [31]. In all of these studies, irinotecan was given as a 90-min infusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Via steps of screening the title and reading the abstract, 6 studies were identified (Van den Brande et al, 2003;Kim et al, 2009;Yokoyama et al, 2009;Zang et al, 2009;Mizushima et al, 2013;Zhu et al, 2011). These studies had been carried out in China, Japan, Korea and Belgium.…”
Section: Resultsmentioning
confidence: 99%
“…CDHP enhances the serum concentration of 5-FU by the inhibiting of dihydropyrimidine dehydrogenase (DPD) 1) , and potassium oxonate inhibits damage of gastrointestinal mucosa 2) . S-1 is reported to be effective for the treatment of various cancers including gastric 3) , pancreas 4) , and colorectal 5) cancers. S-1 is the first drug that improved overall survival in patients with stage II -III gastric cancer as adjuvant therapy 3) .…”
Section: Introductionmentioning
confidence: 99%